Адміністративно-правове забезпечення діяльності місцевих загальних судів в Україні - Прошутя, І. Д.; Proshutia, I. D. (Право і безпека. - 2014. - № 4 (55). - С. 64-70, 2014)
Розкрито співвідношення понять «адміністративно-правове регулювання» та «адміністративно-правове забезпечення». Проаналізовано нормативно-правові акти, що складають основу адміністративно-правового забезпечення діяльності місцевих загальних судів в Україні. Наведено пріоритетні напрямки вдосконалення адміністративно-правового забезпечення діяльності місцевих загальних судів в Україні.

The objective of the article is to review of the current administrative and legal guaranteeing of organization and activity of local general courts in Ukraine, to determine its specificity, nature, significance and to ground the priorities of its development. The author of the article emphasizes that the administrative and legal guaranteeing of local general courts’ activity plays an important role while they realize basic functions – administration of justice. It is stressed that taking into account the current stage of judicial reform in Ukraine and willingness of our state’s leaders to provide an effective and independent judicial branch of power, where organization of the activity inside should be built considering European standards of justice, an important meaning has the study of peculiarities of normative and legal acts that define the basic principles of local general courts’ activity, separation of some issues and finding solutions. It is emphasized that the content of administrative and legal regulation of local general courts’ activity in Ukraine is in realizing the state and powerful, regulatory and organizational, targeted and effective impact with the application of the appropriate arsenal of administrative and legal means to those public relations that arise during their execution by local general courts according to their tasks. It is proved that the feature of administrative and legal regulation of local general courts’ activity is conditioned by the need to streamline and settlement of activity organization and functioning of such courts on the level of the relevant legal acts with the help of specific methods and techniques of various social relations that arise in the process of creating.

Показано соотношение понятий «административно-правовое регулирование» и «административно-правовое обеспечение». Проанализированы нормативно-правовые акты, составляющие основу административно-правового обеспечения деятельности местных общих судов в Украине. Приведены приоритетные направления усовершенствования административно-правового обеспечения деятельности местных общих судов в Украине.
Administrative and Legal Guaranteeing of the Local General Courts’ Activity in Ukraine
Административно-правовое обеспечение деятельности местных общих судов
Прошутя, І. Д. Адміністративно-правове забезпечення діяльності місцевих загальних судів в Україні / І. Д. Прошутя // Право і безпека. - 2014. - № 4 (55). - С. 64-70.
Прошутя І. Д. "Адміністративно-правове забезпечення діяльності місцевих загальних судів в Україні." Право і Безпека 4 (2014): 64-70.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; адміністративно-правове забезпечення; діяльність; місцеві загальні суди; адміністративно-правове регулювання; нормативно-правові акти; удосконалення; administrative and legal guaranteeing; activity; local general courts; administrative and legal regulation; normative and legal acts; improvement; административно-правовое обеспечение; деятельность; местные общие суды; административно-правовое регулирование; нормативно-правовые акты; усовершенствование